Farm growth and land concentration. (April 2022) - Plogmann, Jana; Mußhoff, Oliver; Odening, Martin; Ritter, Matthias
Abstract: Structural change in agriculture is characterized by the interdependency of farms' growth decisions due to the scarcity of agricultural land. This paper adds to the sparse empirical literature on the relation between land market concentration and farm size changes, considering different definitions of the relevant market. Using data from the Integrated Administrative Control System (IACS) from 2005 until 2017 for Brandenburg, Germany, we find that about half of the land transactions occur beyond municipality borders. This emphasizes the importance of carefully defining the relevant market. The descriptive analysis shows that although concentration rates, on average, did not increase over time, spatial differences are present. In the econometric analysis, we apply a two-stage model to analyze how competition for agricultural land impacts the probability and relative level of expansion. For farms that remained active between 2005 and 2017, we find a negative relation between farm size and relative growth. Our conjecture that higher inequality of land distribution fosters the expansion of large farms was not confirmed.